(untitled) (Research, Society and Development, 2023)
The strengthening of the ESG concept has made corporate reputation a crucial factor for the valuation of companies in the stock market, even becoming an object of great interest for investors, especially with regard to anti-corruption practices. Thus, scandals that expose cases of corruption can entail costs and cause companies to devalue in the market. This article aims, therefore, to verify if there is a statistical difference in the behavior of the price of Petrobras shares in normal days and in post-scandal events. For this, a statistical test was carried out from the total data and the dates that the events occurred (day of the event and the following day), using the Z test for two proportions and ANOVA in the studied period. Based on information about the phases of Operation Lava Jato, the dates on which Petrobras was cited were collected. In the Z test, the proportion of rise (or maintenance) and fall in stock prices was compared in two groups: a sample containing all points and a sample containing only news days involving the company. Another analysis was carried out by observing whether the post-event declines are merely occasional, normal falls for the stock, or when there is influence, this fall is more prominent than the normal falls. ANOVA was used as an analysis tool. It was possible to infer, via the Z Test, that the two proportions are the same for the shares, with no statistical evidence that the scandal has an impact on the values. With the F Test, we did not find enough statistical evidence (at 5% significance) to state that falls are more prominent after scandal news.